Development of KOMIDI ALPROF (Komik Digital Mengenal Profesi) to Enhance Learning Interest of Grade IV Students - Lishetiyana, Viriya; Nurdinah Hanifah; Dety Amelia Karlina (Jurnal Elementaria Edukasia, 2025)
This research originated from the issue of low learning interest among fourth-grade students at SDN Pakuwon I, with 28 students as the subjects of the study. The aim of this research is to develop a digital comic-based learning media that can enhance students' interest in learning IPS (Social Studies) material in the 4th-grade class at SDN Pakuwon I. The developed media, named Komidi Alprof (Komik Digital Mengenal Profesi), introduces various professions related to different types of landscapes, in line with the students' everyday life context. The research method used is Research and Development (RnD) with the ADDIE model and a One-Group Pretest-Posttest Design from Pre-Experimental Design. The digital comic media underwent several feasibility tests, including a first material validator with a score of 92.5%, a second material expert with a score of 100%, and a media expert with a score of 91.67%. All three tests indicated that the media was considered “Very Feasible.” The small group trial received a positive response of 84%, the large group trial scored 85%, and the trial in the target school reached 88%, all falling within the “Very Feasible” category. The improvement in students' learning interest was measured using the N-Gain calculation, showing an average pretest score of 46.29% and a posttest score of 67.29%, with a Normalized Gain score of 0.31, categorized as “Moderate.” The results indicate that the Komidi Alprof media is effective in increasing students' interest in learning IPS.